Inclusive green finance: as an approach of developing a comprehensive indicator for BRICS and other emerging economies - Zsuzsanna Novák; Gábor Fáth; Chenhe Ge; Pawan Kumar (Journal of Economic Structures)
Abstract While a large body of literature has provided evidence on how financial development can contribute to the increase in well-being and, more recently, to the quality of the environment, it remains under researched how emerging markets’ performance can be assessed in the two fields simultaneously. The study introduces a novel approach to assessing IGF, using BRICS and four Central European economies as examples to reveal key trends and performance metrics. It evaluates the financial structure of selected economies using World Bank and IMF data sets on financial inclusion, alongside indicators of green finance and innovation. The bunch of data are analysed with the help of three sub-indices contrasting the methodology of the HDI and the positivity constrained version of the two-stage PCA to reach a more stable and consistent evaluation. We find that though the ranking of emerging economies largely depends on the selection of the data set, the composite indicator based on the two-stage PCA provides more balanced results. Overall, the composite indicator developed in this study equips policymakers and international organisations with a practical tool to track progress in financial inclusion and green finance, enabling cross-country comparisons and timely interventions.